POTENSI INTERAKSI OBAT AMLODIPIN PADA PASIEN HIPERTENSI DISALAH SATU PUSKESMAS KABUPATEN SUMEDANG - Anggriani, Ani; Kusumahati, Eva; Mutazam, Irfan Hilmi (Jurnal Riset Kefarmasian Indonesia, 2021)
Hypertension is still a main health problem in indonesia, the purpose of this research is to know the profile of the antihypertensive agent and the interaction potency of the drugs and the relation between the amount of the drugs towards the interaction occurrence in public health centre of sukasari in district of sumedang by the period of July-December 2019. This was observational research with descriptive method. The data collection was performed using drug interaction checker software. There are data of 112 patients. The analysis was performed quantitatively and qualitatively. the result shows the interaction occurrence are happened to woman with percentage of 90% in age group of 65-74 years (30%). Hypertension stage 2 is the most occurred (69%), also there are 82 (73%) patients with potentially might have interaction, meanwhile from all medicines, there are 116 occurrence of interatction might happen. The most interaction occurred happen to amlodipin and hycrochlorothiazide (41%), with pharmacodynamic interaction of 62% and minor severity of 62%.